Management of a Giant Posterior Uterine Leiomyoma: A Case Report - Sonali Hargunani; Varshini; Poonam Nikam (Journal of Clinical and Diagnostic Research, 2025)
Uterine leiomyomas, commonly referred to as fibroids, are the most frequent benign tumours of the uterus, primarily affecting women of reproductive age. Although these tumours are generally asymptomatic, their size and location can lead to significant clinical symptoms, including heavy menstrual bleeding, pelvic pain, and reproductive issues. The patient, a 31-year-old woman with a history of three pregnancies, presented with persistent abdominal pain, increased urinary frequency and dysmenorrhea over the past six months. Physical examination revealed an enlarged uterus corresponding to a 16-week pregnancy size, with a palpable mass suggestive of a uterine abnormality. Pelvic Ultrasound (USG) confirmed the presence of a large leiomyoma measuring 10×8.3×9 cm in the posterior uterine wall. Given the tumour’s size and symptomatic presentation, surgical intervention was deemed necessary. The patient underwent a successful myomectomy, during which the leiomyoma was completely excised without complications. Postoperatively, the patient was closely monitored and discharged in stable condition. The surgical removal of the fibroid resulted in significant relief from her symptoms, improving her overall quality of life. This case underscores the importance of individualized surgical planning in the management of large uterine leiomyomas. The successful excision of the leiomyoma not only alleviated the patient’s symptoms but also preserved her reproductive potential, highlighting the efficacy of surgical intervention in complex cases involving large fibroids.